Embryo transfer of super ovulated and single ovulated llamas at two periods of the year and under field conditions - Pacheco, Joel Iván (2021)
Two embryo production protocols were evaluated: superovulation and single ovulation, determining the collection rate and quality of the embryos, as well as fertility and natality during the reproductive and non-reproductive season, at 4200 meters above sea level and under field conditions. The collection rate of embryos in simple ovulation was 53% (44/83) embryos versus 242.3% (63/26) in superovulation. The quality of the embryos collected by single ovulation was: grade I (90.3 and 83.6%) and grade II (9.4 and 16.7%) and none of grade III; while in superovulation it was: grade I (76.6 and 87.5%), grade II (14.9 and 12.5%) and grade III (8.5 and 0%) for the reproductive and non-reproductive seasons, respectively. Fertility was similar between single ovulation (56.4%) and superovulation (56.0%). The birth rate was 41.1 and 30.0% for single ovulation and superovulation, respectively. It is concluded that both techniques represent a feasible alternative for its application in the high Andean llama rearing systems.